DETERMINATION OF ASPHALT CONCRETE VISCOSITY BY THE FOUR-POINT BENDING TEST - Spínola, J. R.; da Silva, A. C. L.; Torres, A. P.; Frota, C. A.; Frota, H. O. (International Journal of Research -GRANTHAALAYAH, 2019)
In this work, a model for the dynamical four-point bending test is present, with particular emphasis on application to an asphalt concrete (AC) composite, a viscoelastic material, based on the Euler-Bernoulli theory, which approaches an equation where the Young modulus E can be substituted by the operator (E + γ∂/∂t), where γ is an internal damping parameter associated to the binder viscoelasticity and t is the time. As course aggregate in the composition of the AC mixture, the sintered aggregate of calcined clay was used, interesting to be employed as an alternative to the lack of natural course aggregate in some regions of the planet, where the presence of sedimentary rocks prevails. The results indicated that γ decreases with the temperature and loading frequency and the apparent noise in the stiffness versus strain curve is resulted from the natural vibration mode of the beam.